Collaborative product development: The case of network operators - Robin Häberle; Nico Grove (International Telecommunications Society (ITS), 2012)
The goal of this paper is to evaluate the importance of cloud services for Integrated Service Providers and how collaborative product development could strengthen their position within the Cloud Industry. The global cloud market is growing rapidly and gaining daily more momentum. The German Bitkom estimates B2B cloud revenues to exceed 10 bn Euro in Germany by 2016, five times its revenue in 2011. Telecommunication Services - home market to Integrated Service Providers (ISPs) - on the contrary are mostly past their booming years. Even so ISPs are playing a crucial part in the cloud - basically connecting production and consumption - they are typically not mentioned amongst the main Cloud providers. This is puzzling as an integrated network is able to deliver significant unique value in areas such as SLA management, locality, security and intercloud connectivity. To understand this seeming contradiction it is crucial to highlight how the Cloud Value Chain differentiates from the traditional home market of Telecommunication Carriers. Time to market is becoming more and more critical as pure Service Provider (SPs) such as Amazon and Google are entering the market. More and more connectivity - the key competency of ISPs - is seen as commodity and can be treated as given by pure SPs. The authors argue that this weak position of ISPs within the cloud market can be largely explained by too slow product development. The research questions dealt with are: (1) Importance of Cloud Services for ISPs (2) Underlying factors for current performance with Cloud Services (3) Potential contribution of collaborative product development for gaining momentum in the Cloud business...
Keywords: 330